Local and Regional Blocks for Complex Facial Wound Repair - Obokhare, Joy (Facial Plastic Surgery, 2021)
The location, severity, and associated injuries of the head and neck trauma dictate the type and treatment location needed for that particular patient. An in-depth knowledge of local and regional block options is vital to the proper management of facial wounds at the bedside, decreasing need for general anesthesia, anesthesia-related complication, length of hospital stay, and overall hospital costs. This article will discuss local and regional block options for the upper-face, midface, and lower face including dentition; complications of local and regional blocks and how to prevent them; and recent advances in local anesthesia. In addition, conscious sedation as an adjunct to local/regional blocks in children or patients with special needs will be discussed.
Keywords: local anesthesia; regional block; face